LC-MS/MS assay for pitavastatin in human plasma and subsequent application to a clinical study in healthy Chinese volunteers - Tengrui Yin; Qian Liu; Hui Zhao; Lirong Zhao; Hui Liu; Miao Li; Meilan Cui; Wengang Ren (Elsevier, 2014)
A rapid, selective and sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) method has been developed and validated for the determination of pitavastatin in human plasma. Following a liquid-liquid extraction, both the analytes and internal standard telmisartan were separated on a Luna C18 column with a mobile phase consisted of acetonitrile-methanol-1% formic acid in water (50:25:25, v/v/v). Mass spectrometric detection involved electrospray ionization in the positive ion mode followed by multiple reaction monitoring (MRM) of the transitions at m/z 421.9 → 290.1 for pitavastatin and m/z 515.2 → 276.2 for the IS. The assay for pitavastatin showed good linearity (r ≥ 0.99) over the ranges 0.2-400 ng/ml, with a lower limit of quantitation of 0.2 ng/ml. Accuracy and precision for the assay were determined by calculating the intra- and inter-batch variation of quality control (QC) samples at three concentration levels, with relative standard deviations (RSD) of less than 15% for both analytes. The mean extraction recovery of pitavastatin and IS were both above 70%. Matrix effect hasn't been found in this method. The method has been successfully applied to a clinic pharmacokinetic study of pitavastatin administered.